2019
DOI: 10.1155/2019/2974753
|View full text |Cite
|
Sign up to set email alerts
|

Expression of LAIR-1 (CD305) on Human Blood Monocytes as a Marker of Hepatic Cirrhosis Progression

Abstract: Background and Aim. The presumed role of the inhibitory receptor LAIR-1 (CD305) in the inflammatory response suggests that it might contribute to the pathophysiology of chronic inflammatory diseases such as liver cirrhosis. We studied the LAIR-1 expression on liver macrophages and blood monocytes related to the progression of liver cirrhosis. Methods. The expression of LAIR-1 was analyzed by immunohistochemistry, flow cytometry, and Western blot. Results. We found a decreased number of macrophages expressing L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
(55 reference statements)
1
16
0
Order By: Relevance
“…Since an exacerbated inflammatory response might be potentially harmful, the control of the pro-inflammatory mechanisms by an anti-inflammatory counterbalance is an important protective process against further enhancement of inflammation (50,51). Our different in vitro and in vivo models indicate that inflammation leads to an upregulation of LAIR-1, as observed here in monocytes from sepsis patients, but also on circulating monocytes in acute myocardial infarction, rheumatoid arthritis and liver cirrhosis (52)(53)(54). The upregulation of LAIR-1 during inflammation, for instance mediated by TLR or IFN signals, will facilitate its inhibitory signals.…”
Section: Discussionmentioning
confidence: 54%
“…Since an exacerbated inflammatory response might be potentially harmful, the control of the pro-inflammatory mechanisms by an anti-inflammatory counterbalance is an important protective process against further enhancement of inflammation (50,51). Our different in vitro and in vivo models indicate that inflammation leads to an upregulation of LAIR-1, as observed here in monocytes from sepsis patients, but also on circulating monocytes in acute myocardial infarction, rheumatoid arthritis and liver cirrhosis (52)(53)(54). The upregulation of LAIR-1 during inflammation, for instance mediated by TLR or IFN signals, will facilitate its inhibitory signals.…”
Section: Discussionmentioning
confidence: 54%
“…Olde Nordkamp et al (47) found that SP-D binds the leukocyte-associated immunoglobulin-like receptor 1 (LAIR-1), a receptor expressed on most immune cells, including monocytes, and macrophages (76, 77) (Figure 2). SP-D inhibits reactive oxygen species (ROS) production through binding between SP-D collagen domains and LAIR-1 (47).…”
Section: In Vitro Studies Of Sp-d-mediated Cellular Effectsmentioning
confidence: 99%
“…reported that the cross-linking of LAIR-1 with its ligands inhibited the differentiation and activation of B cells induced by B cell receptor cross-linking. 35 However, Liang et al. demonstrated that adaptive immune responses predominated in mild chronic forms of psoriasis such as PsV, while innate and auto-inflammatory responses dominated in acute severe forms such as pustular psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-linking is responsible for the inhibition of inflammatory type I IFN production by monocytes. 35 Type I IFN play an indispensable role in initiating psoriasis through enhancing the development of monocyte-derived DC (moDC), which contributes to Th1 and Th17 differentiation and keratinocyte proliferation. Th1 and Th17 interact with monocytes and instruct monocytes to differentiate into Th1- and Th17-promoting moDCs, leading to the formation of more specialised moDC subsets.…”
Section: Discussionmentioning
confidence: 99%